2012
DOI: 10.1016/j.colsurfa.2012.03.040
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Langmuir and Langmuir–Blodgett films of a calix[7]arene ethyl ester

Abstract: Calixarenes are promising compounds to be used as ionophores and for molecular recognition. Their ability to form Langmuir and Langmuir-Blodgett (LB) films is of great interest in order to obtain small sensor devices which incorporate an active nanometric film. The p-tert-butylcalix [7]arene ethyl ester compound has been synthesised and its ability to form Langmuir and LB films has been shown. This macrocycle forms monolayers but it tends to form multilayers at higher compressions, as corroborated by AFM. BAM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…31,39,40 The difference in the experimentally observed value (135 Å 2 ) may be ascribed to two factors: (i) the theoretical calculations were performed using zero Kelvin temperature, under vacuum, with no water molecules that could H-bond to Calix6 and (ii) repulsion between Calix6 molecules, which is not taken into account in the theoretical modeling. A similar reasoning was adopted by Torrent-Burgués et al 10 for the derivative p-tertbutylcalix [7]arene ethyl ester. A comparison with the literature is not straightforward because the packing of Calix6 molecules appears to depend on the experimental conditions.…”
Section: Langmuir Films Of Calix6 On Pure Watermentioning
confidence: 83%
See 4 more Smart Citations
“…31,39,40 The difference in the experimentally observed value (135 Å 2 ) may be ascribed to two factors: (i) the theoretical calculations were performed using zero Kelvin temperature, under vacuum, with no water molecules that could H-bond to Calix6 and (ii) repulsion between Calix6 molecules, which is not taken into account in the theoretical modeling. A similar reasoning was adopted by Torrent-Burgués et al 10 for the derivative p-tertbutylcalix [7]arene ethyl ester. A comparison with the literature is not straightforward because the packing of Calix6 molecules appears to depend on the experimental conditions.…”
Section: Langmuir Films Of Calix6 On Pure Watermentioning
confidence: 83%
“…It should also be stressed that Calix6 dimers in the multilayers should not contribute to the SFG spectra, since they would have inversion symmetry and therefore a vanishing second-order nonlinear polarizability. The concentration of Cd 2+ ions was chosen based on studies to detect Cd 2+ ions in Langmuir films, since Torrent-Burgués et al 10 observed the isotherms of p-tert-butylcalix[n]arene-ethyl ester (n = 4 and 7) to be affected by Cd 2+ ions at concentrations close to 1 Â 10 À2 mol L À1 .…”
Section: Langmuir Films Of Calix6 On Subphases Containing CD 2+ Ionsmentioning
confidence: 99%
See 3 more Smart Citations